SOME PROBLEMS IN THE DEVELOPMENT OF INTERNAL AND INTERNATIONAL TOURISM - Tukhliev Iskandar Suyunovich; Rahimova Mohinur Jaloliddinovna (Galaxy International Interdisciplinary Research Journal, 2023)
Tourism is divided into categories of internal and international tourism, regardless of the structure of service provision, according to the place of service provision and the group of tourists who consume these services.